Life-history traits of a commercial ray, Raja brachyura from the central western Mediterranean Sea - PORCU, C.; BELLODI, A.; CANNAS, R.; MARONGIU, M. F.; MULAS, A.; FOLLESA, M. C. (Mediterranean Marine Science, 2014)
In the present study the life history of blonde ray Raja brachyura from Sardinian waters (central-western Mediterranean) was investigated and the results compared with previously published data on this species. The age, growth and reproduction were studied using 1792 specimens caught between 2005 and 2013. Females ranged from 13.1 to 105.5 cm in Total length (TL) and males from 18 to 96.5 cm TL. This species was sexually dimorphic, with TL females attaining a larger size than males. Both females and males showed allometric growth (b>3) and we found significant differences in the relationship between length and weight among sexes. The von Bertalanffy growth function (3 parameters), which provided the following values: L∞ = 111.14 cm TL, k = 0.10 and t0 = -1.3 for females, and L∞ = 108.81 cm TL, k = 0.11 and t0 = -1.2 for males, was the best-fit age model. R. brachyura showed a relatively slow growth rate with males slightly more rapid than females. Length and age at maturity were 87.2 cm and 14 years for females and 80.8 cm and 10 years for males. This ray exhibited a restricted reproductive cycle from late May to August, confirmed by the seasonal evolution of GSI values. Ovarian fecundity reached a maximum of 44 yolked follicles. Given the relative abundance in the Sardinian seas, it is hoped that the results can be useful in the implementation of basic management measures in order to ensure the sustainability of catches of this species in the Mediterranean Sea.